Social Networking as an Alternative Environment for Education - Andrei Stanciu; Florin Mihai; Ofelia Aleca (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The main purpose of this research is to analyze the impact of social networks on educational process in Romanian higher education. Employing a theoretical framework regarding the educational value of the social networking web sites, we propose a model of implementing Facebook usage in higher education leaning processes. In order to support our argument, data were gathered through a survey on students and academics at the Bucharest Academy of Economic Studies. Our results reveal that social networking sites have become very popular among students and might be considered as valuable tools for education. The study also opens a wide perspective on students' availability to use social networking sites, but also other web based technologies. While the literature concerning the educational process in Romania is scarce, we contribute by providing empirical evidence about the degree of availability of students and academics in using social networking sites for education.
Keywords: M41; M10; A20; 650; On line social network; e-Learning; Educational context; Facebook; Computer Supported Collaborative Learning